Developing Bilingual Description of Candi Jago and Candi Kidal - Ninda Dzakiyah Maulida (Jurnal Linguistik Terapan, 2022)
This project is a design and development research. The objects of the research are Candi Jago and Candi Kidal. The purposes of this research are (1) to develop bilingual descriptions of Candi Jago and Candi Kidal as integrated in a QR-Code supported by a virtual tour guide application; (2) to give appropriate solutions to the problems. In conducting this design and development research, the stages are analysis, design, development, expert validation, and evaluation. The result of the research is QR-Code that contains bilingual descriptions of Candi Jago and Candi Kidal. The problem in this research was solved by providing the virtual tour guide applications for tourists who go to the object attractions without tour guides.